Novel eco-friendly method to extract keratin from hair - Cassoni, Ana C. (2018)
Pig slaughtering for meat production is a major worldwide industry that generates many byproducts that can cause environmental problems. Nonetheless, it is possible to have a management of these residues toward the reuse and valorization of these byproducts. One opportunity focuses on the extraction of value-added compounds such as keratin since pig hair is composed by 80% of this protein. There are some methods for keratin extraction from human hair as other sources such as wool and feathers, but they bring many problems such as pollution, time-consumption, and high costs. This work uses a commercial detergent belonging to the category of degreasers, capable of fast and efficient dissolution of pig hair, followed by a simple filtration to remove residues from skin trimmings with fat and lard. The resulting solution is submitted to an ultrafiltration process to obtain a solution with higher protein content and purity, both at laboratory scale and pilot scale-up. Use of this keratin green extraction method allows to obtain a keratin product with protein purity up to 70% with a yield extraction of about 50%, which although lower than the previous methods allow protein integrity and cleaner technology. This method allows a relevant valorization of pig hair, using for the first time a simple, cost-effective, and environmentally friendly approach.